The Application of Functional Magnetic Resonance Imaging in an Infant Rat Model of Irritable Bowel Syndrome - Xueping Zhu; Xiaoli Zhu; Weichang Chen; Jianhua Chen (Gastroenterology Research and Practice)
The aim of this study was to use functional magnetic resonance imaging (BOLD-fMRI) to investigate the activated region associated with visceral pain in the brains of infant rats in a model of IBS. Sixteen newborn rats were randomized into an IBS model group and a control group. Those in the IBS group were separated from their mothers and were mechanically immobilized and had rectal sensitization with mustard essential oil for 1 week. The control group had no treatment. After 2 weeks, balloon catheters were inflated with 5 or 10 mL of air in the rectums of both groups. BOLD-fMRI was performed and the data analyzed by imaging software. In the IBS model group, rectal stimulation with 5 mL air distension activated the anterior cingulate cortex, insula cortex (IC), prefrontal cortex (PFC), and thalamus, while 10 mL air significantly activated the ACC, IC, PFC, and thalamus in the model, but not controls. IBS model group was hypersensitive to visceral stimulation by rectal balloon inflation. The major brain areas participating in visceral sensation included the IC, PFC, and thalamus.